The essential guide to getting into medical school - Kalia, Sanjeev; Kalia, Rajiv (Radcliffe Publishing, 2013)
The Essential Guide to Getting into Medical School prepares you for all eventualities, so you can be ready for every aspect of your application and address any shortcomings you may have which may otherwise hinder your chances. It offers helpful tips, tactics, questions and warnings to assist with decision making and personal preparedness. This book is ideal for students of any age, from GCSE onwards, including those applying as postgraduate students. It is also highly recommended for international students wanting detailed advice on how to secure admission